The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.nmd.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and upper limb function as outcome measures in ambulant and non-ambulant subjects with Duchenne muscular dystrophy: A prospective multicentre study

Abstract: The field of translational research in Duchenne muscular dystrophy (DMD) has been transformed in the last decade by a number of therapeutic targets, mostly studied in ambulant patients. A paucity of studies focus on measures that capture the non-ambulant stage of the disease, and the transition between the ambulant and non-ambulant phase. In this prospective natural history study, we report the results of a comprehensive assessment of respiratory, upper limb function and upper limb muscle strength in a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 39 publications
(51 reference statements)
5
33
1
2
Order By: Relevance
“…Estimating yearly rates of decline of PFTs is relevant for clinical management, as it allows to gauge the relative severity of individual decline trajectories, and for the design and interpretation of clinical trials. The FVC decline slope identified in the Italian cohort (−4.2%/year) is in line with previous reports 4,24,25 which estimated values of decline around 5%/year for both FVC and PEF. The decline of PEF, on the other hand, appeared somewhat slower in the Italian cohort (−2.9%/year).…”
Section: Discussionsupporting
confidence: 91%
“…Estimating yearly rates of decline of PFTs is relevant for clinical management, as it allows to gauge the relative severity of individual decline trajectories, and for the design and interpretation of clinical trials. The FVC decline slope identified in the Italian cohort (−4.2%/year) is in line with previous reports 4,24,25 which estimated values of decline around 5%/year for both FVC and PEF. The decline of PEF, on the other hand, appeared somewhat slower in the Italian cohort (−2.9%/year).…”
Section: Discussionsupporting
confidence: 91%
“…We explored the potential use of the Peak Expiratory Flow (PEF) as surrogate of expiratory muscle function in SMA type 2. In other neuromuscular disorders such as Duchenne muscular dystrophy PEF captured respiratory decline earlier than FVC% [28]. In patients with SMA, our novel findings showed that PEF%P declined consistently with FVC%P, confirming its potential utility as a measure of pulmonary function in SMA.…”
Section: A C C E P T E Dsupporting
confidence: 60%
“…Several questions remain to be assessed to fully explore the therapeutic potential of idebenone in the treatment of DMD. A study in younger, predominantly ambulant patients would be useful to investigate the effect of idebenone on non-respiratory muscle, and more specifically on upper limb function which is the main function to preserve in patients with already established respiratory involvement [10] . The combined effect of idebenone and glucocorticoids on respiratory outcomes is currently under investigation in a large randomized, placebo-controlled study (SIDEROS, clinical trials.gov ID: NCT02814019).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal respiratory function, defined as PEF%p or FVC%p falling below 80% of normal, typically occurs at around 10-14 years of age and coincides with the time of loss of ambulation. Thereafter, and over the course of about 10 years both PEF%p and FVC%p follow a co-linear decline [6][7][8][9][10] (reviewed in [4 , 11] ).…”
Section: Introductionmentioning
confidence: 99%